The Role Of Environment In A Region's Sustainable Development As Described By A Butterfly Catastrophe - Vasilis Angelis; Athanasios Angelis-Dimakis; Katerina Dimaki (European Regional Science Association (ERSA), 2012)
The territorial organisation of economies and societies is undergoing a dramatic change. Globalisation, technological innovation, migration and population ageing make it increasingly difficult to predict the future of regions. Economic change tests the ability of all regions to compete and the gap between leading and lagging regions in terms of growth, income and employment is widening. Environmental factors test the ability of national and local governments to manage resources in a sustainable manner and to maintain and improve the quality and safety of life, in areas showing both economic growth (congestion, pollution, contamination, waste generation) or decline (abandoned land, degradation of the built heritage, lack of investment, etc.). These problems have led, step by step, to a modification of the targets of development and the acceptance that the concept of development has to embody the quality of economic growth, as well as its quantity and human well being alongside with economic growth. Sustainable development refers to the ability of our societies to meet the needs of the present without sacrificing the ability of future generations to meet their own needs. Measuring sustainable development means going beyond a purely economic description of human activities; requires integration of economic, social and environmental concerns. New techniques are required in order to benchmark performance, highlight leaders and laggards on various aspects of regional development and facilitate efforts to identify best practices. New tools have to be designed so as to make sustainability decision-making more objective, systematic and rigorous. Our aim is to outline the changing role of environment in a region's development, present a measure of a region's overall attractiveness and incorporate environmental factors into it. The present paper focuses on the environmental factors and its scope is to: Outline the changing role of environment in the process of an area's development over time Present a measure of an area's overall attractiveness Incorporate and quantify the effect of environment in the setting up of this measure
Keywords: C02; C65; Q01; Q51; R58; 330; Region's Image; Region's Attractiveness; Regional Development; Sustainable Development; Economic Factors; Social Factors; Environmental Factors; Butterfly Catastrophe Model